Recipe for persuasion : a novel - Dev, Sonali (William Morrow, an imprint of HarperCollinsPublishers, 2020)
"Chef Ashna Raje thinks that joining the cast of Cooking with the Stars will help save her restaurant and prove to her mother that she's not a failure, but when she's paired with her first love, Rico Silva, the kitchen begins to heat up."--Publisher description.